Предмет: Алгебра,
автор: Discord1ik
Найдите значение выражения (а-9)(а-5)-(а-2)(а+1) при а=-1
Ответы
Автор ответа:
0
a²-5a-9a+45-(a² -a -2) =
a² -14a +45 -a² +a +2 =
=47 -13a =47- 13*(-1) =
= 47 +13 =60
a² -14a +45 -a² +a +2 =
=47 -13a =47- 13*(-1) =
= 47 +13 =60
Автор ответа:
0
a=-1
(a-9)(a-5)-(a-2)(a+1)=a^2-14a+45-a^2+a+2=47-13a
47-13a=47-13(-1)=60
(a-9)(a-5)-(a-2)(a+1)=a^2-14a+45-a^2+a+2=47-13a
47-13a=47-13(-1)=60
Похожие вопросы
Предмет: Математика,
автор: CallMeRuttile
Предмет: Қазақ тiлi,
автор: daniil7713742008z
Предмет: История,
автор: lala4054
Предмет: Алгебра,
автор: 1qwqe21312eqw